ENHANCING WAGE DETERMINATION THROUGH THE IHSAN CONCEPT: STRATEGY TO SOCIAL JUSTICE AND ECONOMIC EQUITY - Syamsuri; Istiqomah, Inna Putri (UIN Sunan Gunung Djati Bandung, 2024)
The determination of regional wage plays a crucial role in mitigating socioeconomic inequalities. However, existing policies often struggle to ensure justice and welfare for all workers. This research proposes the implementation of the concept of Ihsan as an alternative approach to wage determination, emphasizing fairness and individual welfare. Ihsan, which embodies the awareness of Allah’s presence through Muraqabah (self-awareness) and Munadzarah (observational accountability), encourages individuals to act with excellence and integrity in all aspects of life, including economic practices. Despite its potential, the application oh Ihsan in wage policies faces challenges, particularly in aligning the needs of workers with corporate economics demands. This study aims to analyze how the principles of Ihsan can be effectively integrated into wage-setting policies to create a more equitable system. By considering the perspectives of various stakeholders, including workers and business owners, this research seeks to provide a comprehensive understanding of how Ihsan can contribute to social justice and economic balance.